Financial Distress Prediction Using RGEC Model on Foreign Exchange Banks and Non-Foreign Exchange Banks - Laely Aghe Africa (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
The bankruptcy of a company can be marked called Financial Distress, and the company is expected to anticipate the situation. This research aimed to analyze whether the RGEC model can be used to predict Financial Distress on Foreign Exchange Banks and Non-Foreign Exchange Banks. The RGEC model uses several ratios including Risk Profile represented by NPL (Non-Performing Loan) LDR (Loan to Deposit Ratio), GCG is represented by the Composite Value of GCG (Good Corporate Governance), Earnings is represented by ROA (Return On Asset), and Capital is represented by CAR (Capital Adequacy Ratio). It is a quantitative study, with a sample of 185 data of Foreign Exchange Bank and Non-Foreign Exchange ranging from 2013 to 2017, and fulfills this criterion for research from IDX. Logistic regression was used in analyzing data and using SPSS version of IBM 23. The results of the study indicate that NPL, GCG, ROA, and CAR are best used to predict financial distress in Foreign Exchange Bank and Non-Foreign Exchange Bank. The results can be applied to banking companies in determining what policies need to be taken when the company experiences Financial Distress.